The Influence of Depression and Anxiety on Neurological Disability in Multiple Sclerosis Patients - Vitalie Văcăraș; Veronica Văcăraș; Cristina Nistor; Daniela Văcăraș; Adrian Nicolae Opre; Petronela Blaga; Dafin F. Mureșanu (Behavioural Neurology)
Multiple sclerosis (MS) is a demyelinating disease of the central nervous system (CNS), affecting mostly young-aged people. As a chronic incurable disease, in most cases, it can lead to progressive neurological impairment and severe disability. Depression and anxiety are major distress factors for MS patients, being considerably aggravating elements for their functional capacity. In this study, we analysed the mood disorder distribution and the possible correlations between depression, anxiety, automatic negative thoughts, and MS disability. We took into consideration 146 MS patients, who completed a series of questionnaires: Beck Depression Inventory II (BDI-II), Endler Multidimensional Anxiety Scales-State (EMAS-S), and Automatic Thoughts Questionnaire (ATQ). The Expanded Disability Status Scale (EDSS) was used to measure the neurological disability. Of all patients, 30.1% had symptoms for depression and 11% presented suicidal thoughts. After analysing the correlation index between each variable, we found that there is a mild positive correlation between depression and the EDSS score and between anxiety and the EDSS score. A difference is found in the test scores according to the type of the MS disease. Also, automatic negative thoughts are strongly correlated with depression and anxiety, but do not mediate the path between psychological comorbidities and neurological impairment. Sociodemographic features and interferon-beta treatment were not related to the intensity of the mood disorders. The study suggests that depression and anxiety are frequently encountered among MS patients and these mental disfunctions have an impact on their disability. A proper identification of these risk factors may improve the quality of life for these patients.